Analisis Faktor-Faktor yang Mempengaruhi Kepatuhan Perawat dalam Menerapkan Program Pencegahan Pengendalian Infeksi di RSUD Bayung Lencir - Puspasari, Anisa; Gustina, Erma; Rahutami, Syntia (Jurnal Akademika Baiturrahim Jambi, 2024)
Infection Prevention and Control, hereinafter abbreviated to PPI, is an effort to prevent and minimize the occurrence of infections in patients, staff, visitors and the community around health service facilities. Infection prevention and control (PPI) activities in health service facilities are very important to carry out because they are an indicator of service quality standards and are important for patients, health workers and visitors. This study aims to analyze the factors that influence nurses' compliance in implementing the infection control prevention program at Bayung Lencir Regional Hospital, Musi Banyuasin Regency. This research is an analytical study with a cross sectional approach. This research was carried out in February-March 2024. The sampling technique used a total sampling technique of 77 people. Data collection uses a questionnaire sheet. Data analysis carried out was univariate, bivariate and multivariate analysis with the chi-square test. Based on bivariate analysis using the chi-square test, namely knowledge p-value: 0.035, perception p-value: 0.020, barriers to implementing the ppi p-value program: 0.132, workload p-value: 0.002, information and training p-value: 0.010, and availability of facilities and facilities p-value: 0.235. It can be concluded that there is a relationship between knowledge, perception, workload, information and training and infection control prevention programs. It is hoped that this will provide information and input in planning and increase the compliance of nurses and other staff in implementing infection control prevention programs.